Gesetz und Recht - Recht und Gerechtigkeit: Recht und Religion in biblischen Perspektiven - Welker, Michael (Jahrbuch für biblische Theologie, 2023)
Since the 1980s there has been an continuous increase in scholarship in the field of “law and religion studies”, which had previously received only little attention in academia and wider cultural discourses. This contribution is an enquiry into the reasons for this development and ponders how a biblical perspective can contribute to the reorientation at hand. It draws upon the important question about the “core of the law”, put by the legal scholar Harold Berman, and discusses subsequently the reciprocal dynamics between “law, mercy, and pistis” – with attention to questions of legal traditions of the present – in Mt 23:23 and corpora of biblical law.
Online veröffentlicht: 4. Dezember 2023
DOI funktioniert nicht, 08.02.2024
Keywords: Bibel / Matthäusevangelium; Religionswissenschaft; Recht; Berman, Harold Joseph